Non-accidental head injury in young children : medical, legal and social responses - Cobley, Cathy (Jessica Kingsley Publishers, 2007)
This academic research volume will be an exploration of non-accidental head injury in babies and young children, covering medical, social, and legal aspects of this phenomenon, as well as the responsibilities of professionals, child protection agencies and the media in this area. Non-accidental head injury is often referred to as being synonymous with 'shaken baby syndrome' (SBS) - a term which has attracted a great deal of controversy in recent years due to both disagreement about its cause and the reliability of eyewitness testimony. The authors investigate the existing evidence surrounding SBS and its recognition and construction, including medical versus social explanations and the difficulties involved in proving abuse. The reliability of eyewitness and expert testimony are discussed in the context of the concept of proof, as is the social backlash against high profile media cases such as those of Sally Clarke, Trupti Patel and Angela Cannings.; The authors argue for an examination of non-accidental head injury rather than SBS, as this term encompasses other forms of abuse as well as shaking, and caution against a blind acceptance of medical testimony, arguing that this may impede child protection agencies' ability to assess cases objectively and accurately. They also consider the effectiveness of prevention strategies in reducing the incidence of child abuse cases. This insightful book will be essential reading for social workers, lawyers, health professionals, and those working with child protection agencies.